(untitled) (The International Journal for Scientific Research, 2023)
Introduction: Despite the critical role of prehospital management, variations persist in global practices. Recent literature indicates that about 35% of emergency medical services (EMS) providers adhere to established guidelines for spinal immobilization in certain regions. This systematic review aimed to contribute to the ongoing dialogue surrounding the prehospital management of SCIs, ultimately improving outcomes for individuals affected by these traumatic injuries. Methods: A comprehensive literature review was conducted through a systematic search of electronic databases, employing refined search terms and Boolean operators to focus on prehospital management of spinal cord injuries from the inception of each database to July 2023. Inclusion criteria involved original research articles, systematic reviews, and meta-analyses, with a screening process led by two independent reviewers and subsequent data extraction to inform evidence synthesis, accounting for study limitations and bias assessments. Results: This systematic review summarizes findings from eight clinical interventional studies on preventing idiopathic spinal cord injury (SCI) during prehospital emergency aid for traumatized patients. The studies encompassed diverse populations and interventions, revealing variable effectiveness in reducing idiopathic SCI incidence. Notably, specialized protocols for pediatric spinal immobilization and modifications for geriatric patients demonstrated promising effectiveness, emphasizing the importance of age-specific considerations in prehospital care for SCI prevention. Conclusions: The systematic review findings underscore the nuanced nature of prehospital interventions for idiopathic spinal cord injury prevention, emphasizing the importance of age-specific considerations and cautioning against a one-size-fits-all approach, while also highlighting the need for ongoing research to refine protocols and improve patient outcomes given the lack of definitive evidence in favor of early versus delayed immobilization.